3D laparoscopic prostatectomy: A prospective single-surgeon learning curve in the first 200 cases with oncologic and functional results. (4th May 2021) - Haapiainen, Henry; Murtola, Teemu J.; Raitanen, Mika
Abstract: Background: Studies for 3D-laparoscopic prostatectomy (3D-LRP) learning curve and surgical results are lacking. Combining 3D vision to LRP attenuates differences compared to Robotic assisted laparoscopic prostatectomy (RALP) with similar mini-invasiveness but lower costs. Materials and methods: Two hundred consecutive men with localized prostate cancer underwent 3D-LRP at Seinäjoki central hospital between 2013 and 2018. Oncological and functional results were documented. Long-term functional evaluation was done using EPIC-26 survey. Clavien-Dindo classification was used to assess complications during first 3 months. All operations were performed by a single surgeon (M.R.) with no experience of LRP or 3D-LRP. The learning curve was assessed by evaluating urethral anastomosis- and total operative time. Perioperative and postoperative data was collected prospectively during surgery and at subsequent control visits up to minimum of 1 year. Results: A plateau in anastomosis time was reached after 30 cases and in operative time after 60 cases. Median operative time was 114 min (78–258 min) and median time for anastomosis was 25 min (11–90 min). Median blood loss was 150 ml (10–800 ml); 93.5% of the patients were discharged within the first 3 days. Clavien-Dindo ≥3a complications occurred in 6.5%. Positive surgical margins occurred in 23%. One-year after the operation, 93.3% had PSA ≤ 0.1; 91.9% of the patients were dry or used one daytime pad. EPIC-26 scores were as follows: Urinary incontinence 79.25 (14.5–100), urinary irritative/obstructive 93.75 (31.25–100), bowel 100 (33.33–100), sexual 36.17 (0–100) and hormonal 95 (37.5–100). Conclusion: The learning curve for 3D laparoscopic prostatectomy is comparable to RALP, which makes it a cost-effective alternative with comparable oncological and functional results.